Development of thermoplastic toughened hybrid kenaf/glass fibre-reinforced epoxy composite for automotive bumper beam - Makinejad, Majid Davoodi (2012)
Bumper is one of the important safety components of the passenger car. It has to withstand the low-impact collision from the external objects without severe damages as well as absorb the significant impact load during crushing. The estimated annual car productions show 76 million vehicles until 2020, so the End of Life Vehicles (ELV), which is being driven by European Union regulations, enforced the car manufacturers to consider the environmental impact by shifting from synthetic materials to agro-based materials. Hybridization of natural fibres with glass fibres provides a method for mechanical property's improvement. Kenaf is extracted from the bast of the annual fast-growing plant named Hibiscus cannabinus, which is considerably grown in Malaysia. The research initially commenced by investigating the bumper beams in local and imported passenger cars in Malaysia to find geometry (overall dimension, thickness, longitudinal radius), material (type, estimated ingredient, estimated production method) and energy damping system (five damping mechanism). Consequently, the hybrid kenaf/glass epoxy as composite and modified sheet moulding compound (SMC) as manufacturing method is selected. After some preliminary trial, it is concluded that material makes from 2 plies of kenaf and 3 plies of fibre glass, with fibre orientation (0, 90, 0, 90, 0). The fibres are fixed onto a thin steel frame, while they were stretched by a fixture. Epoxy and hardener with 100: 14 wit % sprayed on them and pressed into a controlled heat and pressure sealed steel mould. The results indicated that, apart from impact property, other mechanical properties such as tensile strength, Young's modulus, flexural strength and flexural modulus are comparable with glass mat thermoplastic (GMT). Since the impact property did not fulfill the common bumper beam material GMT, in second step, 5 wit % polybutylene terephthalate (PST) was used to improve the epoxy toughness and impact properties with a low thermo-mechanical drawback. The impact property was improved by only 54%, which was lower than the GMT. The third part of the research concentrated on improving the geometrical structure by selecting the best bumper beam concept to fulfill the safety parameters of the pre-defined product design specification (POS). The mechanical properties of the developed hybrid composite material are considered for whole bumper beam concepts with the same frontal curvature, thickness, and overall dimensions. The low- speed impact test was simulated under the same condition in ABAQUS V 16R9 software. Six weighted criteria consisted of deflection, strain energy, mass, cost, easy manufacturing, and the possibility of the ribs were analyzed to form an evaluation matrix. TOPSIS method was employed to select the best concept. It was concluded that double hat profile (OHP) is a more suitable concept for bumper beam. Finally, the low impact test was carried out to the selected bumper beam concept (OHP) when the vertical strength ribs were added. The results showed that the deflection decreases by 11% and the strain energy increased by 11.3% compare with unribbed bumper beam. Overall, it was concluded that the mechanical properties of the PBT toughened hybrid kenaf/glass epoxy composite under controlled SMC manufacturing method can enhance the structural strength and could be potentially employed in the automotive structural component.